Glycosylation at Asn254 Is Required for the Activation of the PDGF-C Protein - Hu, Wenjie; Zhang, Ruting; Chen, Wei; Lin, Dongyue; Wei, Kun; Li, Jiahui; Zhang, Bo; Li, Xuri; Tang, Zhongshu (Frontiers in Molecular Biosciences, 2021)
Platelet-derived growth factor C (PDGF-C) is a member of PDGF/VEGF family that is well-known for mitogenic effects on multiple cell types. Glycosylation is one of the most important forms of post-translational modification, esp. for secreted proteins and membrane proteins. Glycosylation is well-known for roles in protein procession such as folding, conformation, distribution and stability that happen intracellularly in ER and Golgi apparatus. Despite the fact that the general process and function of glycosylation have been well documented, still more are expected as the glycosylation of many suspected substrates has not been characterized yet. Here we report that PDGF-C protein is glycosylated at three sites: Asn25, Asn55 and Asn254. However, mutants of any of these sites have no effect on the expression and secretion of PDGF-C protein. Disruption of PDGF-C glycosylation does not affect its procession in ER and Golgi apparatus. Instead, N254A mutant abolishes extracellular full-length PDGF-C protein activation and PDGF receptor signaling. Our findings reveals that glycosylation does not affect PDGF-C protein procession but its activation. This study reveals a crucial modification form of PDGF-C protein, and it may shed new light on the function of glycosylation.